SIMD-based parallelized rate distortion optimized quantization for AVS3 - TANG Yixin; HUANG Xiaofeng; TANG Ran; ZHOU Yang; CUI Yan; YIN Haibing (Dianxin kexue)
To improve the coding efficiency of rate-distortion optimization quantization (RDOQ) for the third-generation audio video coding standard (AVS3), a parallelized RDOQ algorithm based on single instruction multiple data (SIMD) was proposed. Firstly, in the optimal coefficient decision (OCD) stage, the dependencies within the scan line were retained through optimization. Secondly, in the last non-zero position decision (LNPD) stage, the Zig-Zag scan line was split into various independent lines based on the partitioning strategy. The optimal coefficients on each scan line were allowed to be calculated in parallel by the proposed method. Finally, SIMD instructions were utilized for parallelized acceleration to boost calculation efficiency in the RDOQ process. Experimental results show that the proposed algorithm can achieve a 29.46% coding time reduction with only 0.25% BD-Rate loss for AI configuration.